Metabolic and growth responses of rainbow trout (Oncorhynchus mykiss) to black soldier fly meal: A meta-analysis and multivariate evaluation of physiological trade-offs - KhaiHang Choong; ZeXin Li; Fui Fui Ching; Leong Seng Lim; Zhou Wu; Karsoon Tan (Aquaculture, 2026)

GC – MS Analysis and Antiviral Efficacy of Lactiplantibacillus plantarum Postbiotic Extracts Against Infectious Haematopoietic Necrosis Virus - Mohammad Tamrin Mohamad Lal; Gilbert Ringgit; Zy Chee Wong; Leong Seng Lim; Fui Fui Ching; Ilham Misbakudin Al Zamzami; Abdul Aziz Jaziri; Muhamad Afiq Aziz; Hiroaki Saito; Motohiko Sano (Journal of Fish Diseases, 2026)
Infectious haematopoietic necrosis virus (IHNV) causes devastating economic losses in salmonid aquaculture and effective control measures are urgently needed. This study investigates the anti‐IHNV potential of postbiotics derived from Lactiplantibacillus plantarum . The crude postbiotic extract (PBP20o) and a neutralized version (PBP20a) were evaluated for cytotoxicity and antiviral activity in epithelioma papulosum cyprini (EPC) cells. Both extracts exhibited a safe concentration threshold of 1.15 μgmL −1 . Remarkably, treatment with PBP20o and PBP20a at this non‐cytotoxic concentration reduced IHNV titers by 0.82 log₁₀TCID₅₀/ml (84.9%) and 0.46 log₁₀TCID₅₀/ml (65.3%), respectively. The enhanced efficacy of the acidic extract might suggest a dual mechanism involving direct acid‐mediated viral inactivation combined with the action of pH‐stable bioactive metabolites. GC–MS identified three potential antiviral compounds, including such as trans‐cinnamic acid (RT = 33.688, A% = 0.39), pyrrolo[1,2‐a]pyrazine‐1,4‐dione, hexahydro‐3‐(2‐methylpropyl) (RT = 48.516, A% = 13.54) and hexadecanamide (RT = 56.226, A% = 3.11) from L. plantarum postbiotic. This study identifies L. plantarum postbiotics as a novel and promising source of antiviral compounds, offering a potential alternative strategy for mitigating IHNV outbreaks in aquaculture while ensuring biosafety for the target host and end consumers.

Reproductive Ecology of the Java Rabbitfish, Siganus javus, in the Southern South China Sea - Takaomi Arai; Iy Vonne Tan; Fui Fui Ching; Norhayati Ahmad (Fishes, 2025)
Fish reproductive biology influences their life history and can impact their vulnerability to fisheries; therefore, for sustainable management and development, a proper understanding is crucial. Reproductive biology, including maturation, spawning season, fecundity, and sex ratio, was examined throughout the year in the Java Rabbitfish, Siganus javus, in the southern South China Sea. This study is the first to examine reproductive traits by collecting a total of 339 S. javus specimens monthly from September 2017 to August 2018 through detailed gonad histology. The spawning season of female S. javus was mainly restricted to July, August, October, and December, whereas male fish were found to spawn throughout the year. Inter-species variations in the spawning season were observed within the genus, which is influenced by interspecific spawning strategies and regional environmental factors. The sex ratio close to 1:1 suggests that the fish population is in equilibrium in the region. The fecundity of S. javus ranged from 1.8 × 105 to 12 × 105, which was similar to that of other species in Siganus, suggesting less inter- and intra-species variation in fecundity within the family. The middle maturation stage was absent throughout the year, probably due to the different habitat uses during their life history. Reproductive biology might influence other biological aspects, such as migration and behaviour in the fish.

Duckweed protein: Extraction, modification, and potential application - Nurul Shaeera Sulaiman; Hana Mohd Zaini; Wan Rosli Wan Ishak; Patricia Matanjun; Ramlah George; Sylvester Mantihal; Fui Fui Ching; Wolyna Pindi (Food Chemistry, 2025)

Embryonic and larval development of backcrossed hybrid grouper between TGGG (Epinephelus fuscoguttatus x E. lanceolatus) and giant grouper (E. lanceolatus) - Sari Asfarina Sariat; Fui Fui Ching; Norfazreena Mohd Faudzi; Shigeharu Senoo (Aquaculture, 2023)

Colour vision in the tropical giant mottled eel Anguilla marmorata as determined by classical conditioning test - Fui Fui Ching; Mercylla Sara Joshua; Gunzo Kawamura; Shigeharu Senoo; Leong-Seng Lim (Ichthyological Research, 2022)

Palm Oil-Based Enriched Diets for the Rotifer, Brachionus plicatilis, Improved the Growth of Asian Seabass (Lates calcarifer) Larvae - Nik Siti Zaimah Safiin; Saleem Mustafa; Fui Fui Ching; Rossita Shapawi (Frontiers in Marine Science, 2021)
Different types and inclusion levels of palm oil were incorporated in the enriched diets of L-type rotifer, Brachionus plicatilis , and fed to Asian seabass ( Lates calcarifer ) larvae. The dietary fish oil was replaced with either 50 or 75% of crude palm oil, CPO (CPO50, CPO75) and refined bleached deodorized palm olein, RPO (RPO50, RPO75). The enriched diet containing 100% fish oil (FO100) was used as the experimental control. Triplicate groups of the fish larvae of initial length 2.72 ± 0.14 mm were fed with enriched rotifer for 15 days. In general, palm oil-based enriched diets performed better than the control diet (FO100). Specifically, final mean body weight (31.3 ± 9.2 mg), final mean total length (11.5 ± 1.6 mm), SGR (29.0 ± 1.4%/day) and WG (7,769.4 ± 1,510.8%) of Asian seabass larvae fed RPO75 were significantly higher ( P < 0.05) compared to those fed the other palm oil-based diet and FO100. The rotifer enriched with palm oil significantly affected the body proximate composition and fatty acid profiles of the fed larvae. The present study suggests that RPO and CPO can be considered as a good alternative dietary lipid for enrichment of rotifer to positively influence the nutritional requirements of the Asian seabass larvae and support their survival and growth.

High-resolution chemical profiling and antiparasitic potential of the tropical shrub Dillenia suffruticosa - Muhammad Dawood Shah; Kazuki Tani; Balu Alagar Venmathi Maran; Yoong Soon Yong; Ching Fui Fui; Sitti Raehanah Muhamad Shaleh; Charles S. Vairappan (Fisheries Science, 2020)

Screening for a Potent Antibacterial Peptide to Treat Mupirocin-Resistant MRSA Skin Infections - Siew Mei Samantha Ng; Hui Si Vivian Ching; GuiFang Xu; Fui Mee Ng; Esther H. Q. Ong; Qiu Ying Lau; Roland Jureen; Jeffrey Hill; C. S. Brian Chia (International Journal of Peptide Research and Therapeutics, 2017)